SYSTEM OF PRINCIPLES IN EDUCATION AND LEARNING ACCORDING TO THE NOVEL “THE HISTORY OF TIGRAN OR MORAL LESSONS FOR ARMENIAN CHILDREN” BY KH. ABOVYAN (Education in the 21st Century, 2024)
The article explores the inheritance of past and contemporary teaching methods within the realm of education, focusing on vital educational issues in the emerging individual education system. Throughout the history of education, aspects such as moral norms, spiritual values, self-government mechanisms, family and social dynamics, aesthetic perception, and cultural worldviews have consistently commanded attention. It is emphasized that the value system of each historical period is primarily shaped by the scientific and aesthetic heritage of that era. Often, modern pedagogical approaches find their foundation in the experiences of the past. Kh. Abovyan's literary-pedagogical legacy, especially exemplified in "History of Tigran or Moral Lessons for Armenian Children," serves as the best evidence of the aforementioned statement. This 19th-century novel-treatise on pedagogy is a repository of unique scientific and pedagogical principles that remain relevant today, applicable to children, parents, and particularly educators as instructive guidelines for implementing educational systems. It provides a fresh perspective on contemporary scientific pedagogical principles and experimental innovations.
Keywords: Education; pedagogical innovations; Khachatur Abovyan; novel-treatise pedagogy; edification and advice; material value; moral value; family subordination; personality formation